PERAN BAWASLU DALAM MENINGKATKAN PERAN AKTIF MASYARAKAT DALAM PENGAWASAN PARTISIPATIF PILKADA 2024 DI JAWA BARAT MELALUI FORUM WARGA - Pagiling, Gerald Arung (Jurnal Keadilan Pemilu, 2024)
The 2024 Regional Head Election (Pilkada) is the first to be held simultaneously in Indonesia. This Pilkada is an important moment in democracy that requires active participation from all elements of society. The role of the Election Supervisory Body (Bawaslu) is very important in ensuring that this Pilkada can run honestly, fairly, and transparently. This article aims to analyze the role of Bawaslu in improving participatory supervision in the 2024 Pilkada in West Java through the Citizens' Forum. This Citizens' Forum is a forum for community discussion and coordination which is considered an effective means to strengthen participatory supervision. The research method used is a literature study. The results of this study indicate that Bawaslu seeks to facilitate the community in actively participating through voter education, supervision training, and the formation of a citizen forum network. This study concludes that participatory supervision through the Citizens' Forum will make a significant contribution to ensuring a more transparent and accountable Pilkada in West Java.